Lithium-based negative electrode material as well as preparation method and application thereof
Through multi-source vacuum thermal evaporation technology, the fluoride hybrid SEI layer of the lotus structure is constructed on the surface of the lithium metal negative electrode, which solves the problems of taking into account both mechanical strength and ionic conductivity of the lithium metal negative electrode, and significantly improves the cycle stability and electrochemical performance of the battery.
Patent Information
- Application Number
- CN202411891920.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing lithium metal negative electrodes are difficult to overcome the defects of solid electrolyte interface (SEI), especially in terms of mechanical strength and ionic conductivity, resulting in poor cyclic stability and electrochemical performance.
Through multi-source vacuum thermal evaporation technology, a dense uniform fluoride hybrid SEI layer of the lotus candle structure is constructed on the surface of lithium metal, and the mechanical properties and ion diffusion properties are optimized using the collaborative composite of fluoride materials such as LiF, CeF3 and LaF3.
It significantly improves the cycle stability and electrochemical performance of lithium metal negative electrodes, extends the cycle life, reduces dendrite growth and interface side reactions, and improves the safety and high energy density characteristics of the battery.
Smart Images

Figure CN119725385A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium metal negative electrode, and in particular to a lithium-based negative electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy technologies, the research and application of high energy density batteries have received increasing attention. Lithium metal anodes are regarded as ideal anode materials for next-generation high energy density batteries due to their high theoretical specific capacity and low lithium insertion potential. However, lithium metal anodes face a series of challenges in practical applications, especially in terms of cycle stability.
[0003] During the battery cycle, the lithium metal negative electrode easily reacts with the electrolyte to form an unstable solid electrolyte interface (SEI). This interface layer has a crucial impact on the performance of the battery. However, existing SEIs usually have multiple defects, such as low mechanical strength, which easily leads to the growth of lithium dendrites, which in turn causes internal short circuits and safety hazards in the battery; low ionic conductivity, which limits the efficient diffusion and uniform deposition of lithium ions, affecting the battery's charge and discharge performance and cycle life; poor interface contact, resulting in electrolyte penetration and increased interface impedance, further exacerbating the degradation of battery performance.
[0004] In order to overcome these defects, researchers have tried to optimize the performance of lithium metal anodes by constructing artificial SEI. Among them, fluoride materials represented by lithium fluoride (LiF) have attracted much attention due to their high mechanical strength and excellent ionic conductivity. However, the commonly used fluoride artificial SEI often has shortcomings in performance and it is difficult to meet the requirements of high mechanical strength and high ionic conductivity at the same time.
[0005] At present, the methods for preparing artificial SEI mainly include liquid phase chemical methods, vapor phase chemical deposition and atomic layer deposition. Although the liquid phase chemical method is simple and easy to operate, it is difficult to control the interface uniformity, thickness and composition distribution, is prone to generate impurity byproducts, and has high requirements for the reaction environment, resulting in a decrease in the stability of the protective layer. Although vapor phase chemical deposition and atomic layer deposition methods can produce high-quality films, the equipment is expensive, the process is complex, the efficiency is low, and a gas precursor is required for the preparation of fluorinated SEI. The process is limited by the selectivity and safety of the reaction gas, and is not suitable for large-scale and large-scale industrial preparation.
[0006] Therefore, it is particularly important to develop an artificial SEI preparation technology that can overcome the existing SEI defects, take into account both high mechanical strength and high ionic conductivity, and is suitable for industrial preparation. Summary of the invention
[0007] The technical problem to be solved by the present invention is that it is difficult for existing lithium metal negative electrodes to overcome SEI defects and meet the requirements of high mechanical strength and high ionic conductivity. The purpose is to provide a lithium-based negative electrode material and its preparation method and application, which overcomes SEI defects, takes into account high mechanical strength and high ionic conductivity, significantly improves the cycle life and electrochemical performance of lithium metal negative electrodes, and provides strong support for the research and development of the next generation of high energy density batteries.
[0008] The present invention is achieved through the following technical solutions:
[0009] A method for preparing a lithium-based negative electrode material comprises the following steps:
[0010] Different fluoride evaporation sources were ground and placed under the lithium foil substrate;
[0011] Open the evaporation source baffle and adjust the process parameters of the evaporation process;
[0012] Pre-dissolving each fluoride evaporation source;
[0013] The substrate baffle is opened to keep the lithium foil substrate rotating, and fluorinated SEI is evaporated on the surface of the lithium foil substrate to obtain a lithium-based negative electrode material.
[0014] As a possible design, the fluoride includes at least two of LiF, LaF3 and CeF3.
[0015] As a possible design, the above-mentioned fluoride includes two raw materials, one is LiF and the other is LaF3 or CeF3.
[0016] As a possible design, during the above evaporation, the vacuum degree is less than 10 -5 Pa, the evaporation temperature of the fluoride evaporation source is 500-1450℃, and the evaporation rate is The temperature of the lithium metal substrate was maintained at 25-50°C.
[0017] As a possible design, the above-mentioned pre-dissolving treatment of each fluoride evaporation source specifically includes the following steps:
[0018] Open the baffles of each fluoride evaporation source, keep the substrate baffle closed, start heating each fluoride evaporation source at the same time, keep the evaporation flow rate at 0, gradually adjust the crucible heating power, and perform a pre-dissolution. The pre-dissolution time is t1. At this time, the pre-dissolution temperature of each fluoride evaporation source reaches T 1x , keep heating t2;
[0019] Each fluoride evaporation source is pre-dissolved for a second time, and the pre-dissolution time is t3. At this time, the pre-dissolution temperature of each fluoride evaporation source reaches T 2x , keep heating t4, wherein X is each fluoride.
[0020] As a possible design, after the above LiF is pre-dissolved once, the pre-dissolved temperature T 1LiF 550-650℃; After CeF3 is pre-dissolved once, the pre-dissolved temperature T 1CeF3 1100-1150℃; After LaF3 is pre-dissolved once, the pre-dissolved temperature T 1LaF3 1150-1250℃;
[0021] After the above LiF is pre-dissolved twice, the pre-dissolved temperature T 2LiF 850-950℃; After the second pre-dissolution of CeF3, the pre-dissolution temperature T 2CeF3 is 1200-1300℃; after LaF3 is pre-dissolved for the second time, the pre-dissolved temperature is T 2LaF3 It is 1300-1400℃.
[0022] As a possible design, the rotation rate of the lithium foil substrate is maintained at 4-6 r / min.
[0023] As a possible design, the thickness of the fluorinated SEI is 200-300 nm, and the fluorinated SEI is a lotus pod structure.
[0024] In a second aspect, the present invention provides a lithium-based negative electrode material prepared by the above-mentioned preparation method.
[0025] In a third aspect, the present invention provides an application of a lithium-based negative electrode material prepared by the above-mentioned preparation method in battery materials.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0027] Based on the uniformity advantage of vapor deposition, the present invention develops vacuum thermal evaporation technology to the preparation of multi-source fluoride solid electrolyte interface for lithium metal negative electrode, realizes multi-component synergistic composite of fluoride materials by synergizing the structure and properties of the multi-source fluoride interface, and further realizes the synergistic optimization of mechanical properties and ion kinetic properties, constructs a lotus-shaped fluoride hybrid solid electrolyte interface with both high mechanical strength and high ionic conductivity, thereby significantly improving the cycle stability and electrochemical properties of lithium metal negative electrode, and solves the problems of uncontrolled lithium dendrite growth caused by insufficient SEI mechanical properties, uneven deposition caused by limited lithium ion diffusion, interface side reactions caused by electrolyte corrosion, and interface layer failure caused by volume expansion.
[0028] The lithium-based negative electrode material of the present invention has a capacity retention rate of more than 75% when cycled 1000 times at a 1C rate in a lithium iron phosphate button battery, and has a capacity retention rate of more than 75% at a 1 mA cm -2Lithium deposition under a current of 20 minutes does not generate obvious dendrites. In addition, the technology is highly efficient and can complete the preparation of a 300nm thick fluoride layer within 8 minutes without any harmful byproducts, making it suitable for large-scale industrial production. The structurally and multifunctionally designed SEI provides comprehensive protection for the lithium metal anode, significantly improving the cycle stability and safety of the lithium metal anode, and providing a reliable new solution for the realization of high-performance lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0030] Figure 1 Schematic diagram of the design principle of the lithium-based negative electrode material of the present invention;
[0031] Figure 2 It is a long cycle performance diagram of LiF-CeF3@Li|LFP, LiF-LaF3@Li|LFP and bare Li|LFP batteries of the present invention at 1C rate;
[0032] Figure 3 The LiF-LaF3@Li, LiF-CeF3@Li and bare Li negative electrodes of the present invention are 1 mA cm -2 In situ optical images after deposition for different times at a constant current density. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0034] Existing lithium metal negative electrode materials have problems such as uncontrolled lithium dendrite growth caused by insufficient SEI mechanical properties, uneven deposition caused by limited lithium ion diffusion, interfacial side reactions caused by electrolyte corrosion, and interfacial layer failure caused by volume expansion. In addition, existing liquid phase or single-source deposition methods are difficult to achieve uniform composite at the nanoscale, and the SEI layer often has problems of uneven thickness or unstable composition distribution.
[0035] The present invention adopts multi-source vacuum thermal evaporation technology and independently regulates the evaporation rate and deposition power of multiple fluorides (LiF, CeF3, LaF3) to accurately construct a dense and uniform fluoride hybrid SEI layer with a lotus structure on the surface of lithium metal, thereby achieving coordinated optimization of mechanical properties, ion diffusion and chemical stability, so that the SEI layer has mechanical support properties, ion diffusion channels and chemical passivation barriers.
[0036] A method for preparing a lithium-based negative electrode material comprises the following steps:
[0037] S1. Grind different fluoride evaporation sources and place them under the lithium foil substrate so that the evaporation current can cover the surface of the lithium foil substrate.
[0038] In some embodiments of the present invention, the fluoride includes at least two of LiF, LaF3 and CeF3.
[0039] LiF evaporation can improve the high mechanical strength and dendrite suppression ability of the negative electrode material; LaF3 and CeF3 evaporation can improve the ionic conductivity and chemical stability of the negative electrode material.
[0040] Preferably, the above fluoride comprises two raw materials, one is LiF and the other is LaF3 or CeF3.
[0041] Preferably, the above fluoride includes LiF and LaF3.
[0042] Preferably, the above fluoride includes LiF and CeF3.
[0043] Preferably, the fluoride is ground to micron level.
[0044] Preferably, the fluoride is ground and then placed in a high-purity tungsten crucible for evaporation to ensure that the material is pure and free of impurities.
[0045] Preferably, the lithium foil substrate is fixed 30-50 cm above the fluoride evaporation source so that the evaporation current can evenly cover the substrate surface.
[0046] S2. Adjust the process parameters of the evaporation process.
[0047] In some embodiments of the present invention, during the above evaporation, the vacuum degree is less than 10 -5 Pa, the evaporation temperature of the fluoride evaporation source is 500-2200℃, and the evaporation rate is The temperature of the lithium metal substrate was maintained at 25-50°C.
[0048] Vacuum degree less than 10 -5 Pa can avoid interference from oxygen or moisture, ensuring the high purity of the fluoride layer.
[0049] Preferably, when evaporating LiF, the evaporation temperature is 850-950°C and the evaporation rate is When LaF3 or CeF3 is evaporated, the evaporation temperature is 1200-1300℃ and the evaporation rate is More preferably, when LaF3 is evaporated, the evaporation temperature is 1300-1400°C.
[0050] When the evaporation parameters are within this range, a fluorinated SEI with excellent performance can be prepared.
[0051] S3. Open the evaporation source baffle and perform pre-dissolution treatment on each fluoride evaporation source.
[0052] In some embodiments of the present invention, the above-mentioned pre-dissolving treatment of each fluoride evaporation source specifically includes the following steps:
[0053] S31, open the evaporation source baffle, keep the substrate baffle closed, start heating each fluoride evaporation source at the same time, monitor in real time and keep the evaporation flow rate at 0, gradually adjust the crucible heating power, perform a pre-dissolution, the pre-dissolution time is t1, at this time the pre-dissolution temperature of each fluoride evaporation source reaches T 1x (X=LiF, CeF3, LaF3), keep heating t2, the temperature of the evaporation source reaches the critical temperature close to evaporation.
[0054] After the first pre-dissolution from t1 to t2, the temperature of the evaporation source reaches the temperature close to evaporation; after the second pre-dissolution from t3 to t4, the temperature of the evaporation source reaches the temperature of the target evaporation rate. After two pre-dissolutions, the fluoride can be fully mixed before being deposited on the lithium metal negative electrode, and a stable target evaporation rate can be achieved, which is conducive to uniform deposition after the substrate baffle is opened.
[0055] S32, each fluoride evaporation source is pre-dissolved for a second time, and the pre-dissolution time is t3. At this time, the pre-dissolution temperature of each fluoride evaporation source reaches T 2x (X=LiF, CeF3, LaF3), keep heating t4, the temperature of the evaporation source reaches the critical temperature of the target evaporation rate.
[0056] Preferably, the sum of t1, t2, t3 and t4 of the above-mentioned pre-dissolution treatment is 10-16 minutes.
[0057] The pre-dissolution treatment ensures that all evaporation sources work stably and the power does not fluctuate significantly, which can ensure that the proportion of each component can be controlled during the next stage of evaporation.
[0058] Preferably, t1 is 2-4 min, t2 is 2-4 min, t3 is 2-4 min, and t4 is 2-4 min.
[0059] In some embodiments of the present invention, after the LiF is pre-dissolved once, the pre-dissolved temperature T1LiF 550-650℃; After CeF3 is pre-dissolved once, the pre-dissolved temperature is T 1CeF3 1050-1150℃; After LaF3 is pre-dissolved once, the pre-dissolved temperature T 1LaF3 1150-1250℃;
[0060] After the above LiF is pre-dissolved twice, the pre-dissolved temperature T 2LiF 850-950℃; After the second pre-dissolution of CeF3, the pre-dissolution temperature T 2CeF3 is 1200-1300℃; after LaF3 is pre-dissolved for the second time, the pre-dissolved temperature is T 2LaF3 It is 1300-1400℃.
[0061] S4. Open the evaporation source baffle and the substrate baffle to keep the lithium foil substrate rotating, and at the same time, adjust the evaporation temperature of each fluoride evaporation source to evaporate the fluorinated SEI on the surface of the lithium foil substrate to obtain a lithium-based negative electrode material.
[0062] By rotating the lithium foil substrate and depositing the SEI of mixed fluorides on the surface of the lithium foil substrate, the multifunctional synergy of mechanical support, ionic conductivity and chemical protection can be achieved.
[0063] In some embodiments of the present invention, the rotation rate of the lithium foil substrate is maintained at 4-6 r / min.
[0064] In some embodiments of the present invention, the fluorinated SEI has a thickness of 200-300 nm and is a lotus pod structure.
[0065] LiF provides high mechanical strength, while CeF3 / LaF3 enhances ionic conductivity and chemical stability, forming a strong and dense lotus-shaped multifunctional SEI, which effectively inhibits dendrite growth and optimizes ion transport pathways.
[0066] Preferably, the method further comprises step S5, after the evaporation is completed, cooling the lithium foil and storing it in a water-free and oxygen-free environment.
[0067] Slowly cooling the lithium metal sheet to room temperature and storing it in a water-free and oxygen-free environment can prevent the fluoride layer from oxidation or hydrolysis.
[0068] Example 1
[0069] A method for preparing a lithium-based negative electrode material comprises the following steps:
[0070] S1. Grind LiF and CeF3 into micron-sized powders respectively, and put them into high-purity tungsten crucibles respectively, and fix the lithium foil substrate 40 cm above the crucible;
[0071] S2. Use a high vacuum pump to adjust the vacuum degree of the evaporation chamber to 10 -5Pa, set the LiF crucible evaporation temperature: 950 ° C, evaporation rate Set CeF3 crucible: 1300℃, evaporation rate The temperature of the lithium metal substrate is controlled to be maintained at 25-50°C;
[0072] S3, open the evaporation source baffle, keep the substrate baffle closed, and start heating the LiF and CeF3 evaporation sources at the same time; perform a pre-dissolution for 2 minutes, the LiF and CeF3 evaporation sources reach the pre-dissolution temperature of 550°C and 1100°C respectively, keep heating for 2 minutes, monitor in real time and keep the evaporation flow rate at 0; perform a second pre-dissolution for 2 minutes, the LiF and CeF3 evaporation sources reach the pre-dissolution temperature of 950°C and 1300°C respectively and keep heating for 2 minutes, and the thickness of the obtained fluoride layer is 300nm;
[0073] S4, set the substrate stage to maintain a rotation rate of 5r / min, and adjust the evaporation power of LiF and CeF3 to keep the evaporation rate stable at and The substrate baffle was opened, and 200 nm lotus-shaped LiF-CeF3 artificial SEI with different components was deposited on the substrate surface to obtain lithium-based negative electrode materials;
[0074] S5. After the evaporation is completed, the metal lithium sheet is slowly cooled to room temperature and stored in a water-free and oxygen-free environment.
[0075] Example 2
[0076] A method for preparing a lithium-based negative electrode material comprises the following steps:
[0077] S1. Grind LiF and CeF3 into micron-sized powders respectively, and put them into high-purity tungsten crucibles respectively, and fix the lithium foil substrate 30 cm above the crucible;
[0078] S2. Use a high vacuum pump to adjust the vacuum degree of the evaporation chamber to 10 -5 Pa below, set the LiF crucible evaporation temperature: 900 ° C, evaporation rate Set CeF3 crucible: 1250℃, evaporation rate The temperature of the lithium metal substrate is controlled to be maintained at 25-50°C;
[0079] S3, while keeping the substrate baffle closed, start heating the LiF and CeF3 evaporation sources at the same time; perform a pre-dissolution for 4 minutes, the LiF and CeF3 evaporation sources reach the pre-dissolution temperatures of 600°C and 1100°C respectively, keep heating for 4 minutes, monitor in real time and keep the evaporation flow rate at 0; perform a second pre-dissolution for 4 minutes, the LiF and CeF3 evaporation sources reach the pre-dissolution temperatures of 900°C and 1250°C respectively and keep heating for 4 minutes;
[0080] S4, set the substrate stage to maintain a rotation rate of 5r / min, and adjust the evaporation power of LiF and CeF3 to keep the evaporation rate at and The substrate baffle was opened, and 300 nm lotus-shaped LiF-CeF3 artificial SEI with different components was deposited on the substrate surface to obtain lithium-based negative electrode materials;
[0081] S5. After the evaporation is completed, the metal lithium sheet is slowly cooled to room temperature and stored in a water-free and oxygen-free environment.
[0082] Example 3
[0083] A method for preparing a lithium-based negative electrode material comprises the following steps:
[0084] S1. Grind LiF and CeF3 into micron-sized powders respectively, and put them into high-purity tungsten crucibles respectively, and fix the lithium foil substrate 50 cm above the crucible;
[0085] S2. Use a high vacuum pump to adjust the vacuum degree of the evaporation chamber to 10 -5 Pa below, set the LiF crucible evaporation temperature: 850 ° C, evaporation rate Set CeF3 crucible: 1200℃, evaporation rate The temperature of the lithium metal substrate is controlled to be maintained at 25-50°C;
[0086] S3, open the evaporation source baffle, keep the substrate baffle closed, and start heating the LiF and CeF3 evaporation sources at the same time; perform a pre-dissolution for 3 minutes, the LiF and CeF3 evaporation sources reach the pre-dissolution temperature of 550°C and 1100°C respectively, keep heating for 3 minutes, monitor in real time and keep the evaporation flow rate at 0; perform a second pre-dissolution for 3 minutes, the LiF and CeF3 evaporation sources reach the pre-dissolution temperature of 850°C and 1200°C respectively, and keep heating for 3 minutes;
[0087] S4, set the substrate stage to maintain a rotation rate of 5r / min, and adjust the evaporation power of LiF and CeF3 to keep the evaporation rate stable at and The substrate baffle is opened, and 250nm lotus-shaped LiF-CeF3 artificial SEI with different components is deposited on the substrate surface to obtain a lithium-based negative electrode material;
[0088] S5. After the evaporation is completed, the metal lithium sheet is slowly cooled to room temperature and stored in a water-free and oxygen-free environment.
[0089] Example 4
[0090] A method for preparing a lithium-based negative electrode material comprises the following steps:
[0091] S1. Grind LiF and LaF3 into micron-sized powders respectively, and put them into high-purity tungsten crucibles respectively, and fix the lithium foil substrate 40 cm above the crucible;
[0092] S2. Use a high vacuum pump to adjust the vacuum degree of the evaporation chamber to 10 -5 Pa or less. Set the LiF crucible evaporation temperature to 850°C and the evaporation rate to Setting LaF3 crucible: 1200℃, evaporation rate The temperature of the lithium metal substrate is controlled to be maintained at 25-50°C;
[0093] S3, open the evaporation source baffle, keep the substrate baffle closed, and start heating the LiF and LaF3 evaporation sources at the same time; perform a pre-dissolution for 4 minutes, the LiF and LaF3 evaporation sources reach the pre-dissolution temperature of 200°C and 1300°C respectively, and maintain for 4 minutes, and monitor in real time and keep the evaporation flow rate at 0; perform a second pre-dissolution for 4 minutes, the LiF and LaF3 evaporation sources reach the pre-dissolution temperature of 850°C and 1200°C respectively, and maintain the heating time for 4 minutes;
[0094] S4, open the evaporation source baffle and substrate baffle, keep the substrate stage rotating at 6r / min, and adjust the evaporation power of LiF and CeF3 to keep the evaporation rate stable at and The substrate baffle was opened, and 300 nm lotus-shaped LiF-LaF3 artificial SEI with different components was deposited on the substrate surface to obtain lithium-based negative electrode materials;
[0095] S5. After the evaporation is completed, the metal lithium sheet is slowly cooled to room temperature and stored in a water-free and oxygen-free environment.
[0096] Comparative Example 1
[0097] This comparative example is basically the same as Example 4, except that only LiF evaporation is used.
[0098] Comparative Example 2
[0099] This comparative example is basically the same as Example 4, except that only LaF3 evaporation is used.
[0100] Comparative Example 3
[0101] This comparative example is basically the same as Example 4, except that only NaF evaporation is used.
[0102] Experimental Example 1
[0103] The lithium-based negative electrode material (named LiF-CeF3@Li) of Example 1 and the lithium iron phosphate positive electrode (named LFP) were assembled into a button cell (named LiF-CeF3@Li|LFP); the lithium-based negative electrode material (named LiF-LaF3@Li) of Example 4 and the lithium iron phosphate positive electrode (named LFP) were assembled into a button cell (named LiF-LaF3@Li|LFP). Both of them were compared with the button cell (named bare Li|LFP) assembled with the bare lithium foil substrate (named bare Li) and the lithium iron phosphate positive electrode, and the long cycle performance data were measured at 1C and 2C rates, respectively. The results are shown in Tables 1 and Figure 2 shown.
[0104] LiF-CeF3@Li, LiF-LaF3@Li|LFP and bare Li were subjected to 1 mA cm -2 After deposition at a constant current density of 10 min and 20 min, in-situ optical detection was performed. The results are as follows Figure 3 shown.
[0105] Table 1 Long cycle performance data of LiF-CeF3@Li|LFP and bare Li|LFP batteries at 1C and 2C rates
[0106]
[0107]
[0108] It can be seen from Table 1 that the capacity retention rate is more than 75% after 800 cycles at a 2C rate. Compared with the 1C rate and 1000 cycles, the capacity retention rate of the battery assembled with the lithium-based negative electrode material of Example 1 is much greater than the capacity retention rate of the battery assembled with the bare lithium foil substrate. And compared with the battery cycle capacity of the battery assembled with the lithium-based negative electrode material of Example 1 at a large rate of 2C, it is much greater than the battery cycle capacity of the battery assembled with the bare lithium foil substrate.
[0109] Reference Figure 2 The lithium-based anode material (named LiF-CeF3@Li) and the lithium iron phosphate cathode (named LFP) were assembled into a button cell (named LiF-CeF3@Li|LFP), which was cycled 1000 times at a 1C rate with a capacity of more than 95 mA cm -2 The lithium-based negative electrode material (named LiF-LaF3@Li) and the lithium iron phosphate positive electrode (named LFP) were assembled into a button cell (named LiF-LaF3@Li|LFP) with a capacity of more than 95 mA cm -2, and the capacity retention rate of both is over 75%. Compared with the button cell assembled with bare lithium foil substrate (named bare Li) and lithium iron phosphate cathode (named bare Li|LFP), the capacity is only 46.9 mA cm after 1000 cycles at 1C rate. -2 , the capacity retention rate is only 38.4%.
[0110] Reference Figure 3 , LiF-CeF3@Li at 1mA cm -2 Lithium deposition for 10 min at a current of 1 mA cm-1 showed no obvious dendrite formation; LiF-LaF3@Li|LFP -2 There was no obvious dendrite formation when lithium was deposited for 20 min at a current of 1 mA cm -2 The lithium deposition under the current of 10min showed obvious dendrite formation. This shows that the deposition of LiF-LaF3 or LiF-CeF3 can inhibit the growth of lithium dendrites of lithium negative electrode materials and improve the mechanical properties of SEI.
[0111] Experimental Example 2
[0112] The samples of Comparative Examples 1-3, Example 1 and Example 4 were tested for thickness, mechanical strength and chemical stability. The results are shown in Table 2.
[0113] Table 2
[0114]
[0115] It can be seen from Table 2 that the comprehensive performance of Example 4 is the best, which means that the optimal number of cycles can only be achieved when LiF, LaF3 and CeF3 are evaporated together.
[0116] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a lithium-based negative electrode material, characterized in that: The steps include: Different fluoride evaporation sources were ground and placed under the lithium foil substrate; Adjust the process parameters of the evaporation process; Open the evaporation source baffle and pre-dissolve each fluoride evaporation source; The substrate baffle is opened to keep the lithium foil substrate rotating, and fluorinated SEI is evaporated on the surface of the lithium foil substrate to obtain a lithium-based negative electrode material.
2. The method for preparing a lithium-based negative electrode material according to claim 1, characterized in that: The fluoride includes at least two of LiF, LaF3 and CeF3.
3. The method for preparing a lithium-based negative electrode material according to claim 2, characterized in that: The fluoride comprises two raw materials, one is LiF and the other is LaF3 or CeF3.
4. The method for preparing a lithium-based negative electrode material according to claim 1, characterized in that: During the evaporation, the vacuum degree is less than 10 -5 Pa, the evaporation temperature of the fluoride evaporation source is 500-1450℃, and the evaporation rate is The temperature of the lithium metal substrate was maintained at 25-50°C.
5. The method for preparing a lithium-based negative electrode material according to claim 2, characterized in that: The pre-dissolving treatment of each fluoride evaporation source specifically comprises the following steps: Open the baffles of each fluoride evaporation source, keep the substrate baffle closed, and start heating each fluoride evaporation source at the same time, keep the evaporation flow rate at 0, and perform a pre-dissolution. The pre-dissolution time is t1. At this time, the pre-dissolution temperature of each fluoride evaporation source reaches T 1x , keep heating t2; Each fluoride evaporation source is pre-dissolved for a second time, and the pre-dissolution time is t3. At this time, the pre-dissolution temperature of each fluoride evaporation source reaches T 2x , keep heating t4, wherein X is each fluoride.
6. The method for preparing a lithium-based negative electrode material according to claim 5, characterized in that: After the LiF is pre-dissolved once, the pre-dissolved temperature T 1LiF 550-600℃; After CeF3 is pre-dissolved once, the pre-dissolved temperature T 1CeF3 1100-1150℃; After LaF3 is pre-dissolved once, the pre-dissolved temperature T 1LaF3 1150-1250℃; After the LiF is pre-dissolved for the second time, the pre-dissolved temperature T 2LiF 850-950℃; After the second pre-dissolution of CeF3, the pre-dissolution temperature T 2CeF3 is 1200-1300℃; after LaF3 is pre-dissolved for the second time, the pre-dissolved temperature is T 2LaF3 It is 1300-1400℃.
7. The method for preparing a lithium-based negative electrode material according to claim 1, characterized in that: The rotation rate of the lithium foil substrate was maintained at 4-6 r / min.
8. The method for preparing a lithium-based negative electrode material according to claim 1, characterized in that: The thickness of the fluorinated SEI is 200-300 nm, and the fluorinated SEI is a lotus pod structure.
9. A lithium-based negative electrode material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of a lithium-based negative electrode material prepared by the preparation method according to any one of claims 1 to 8 in the preparation of battery materials.
Citation Information
Patent Citations
Preparation method of lithium ion battery positive electrode material
CN104051727A
Deposition of lithium fluoride on lithium metal surface and lithium secondary battery using same
CN109565039A
Application of metal fluoride in silicon oxide negative electrode of lithium ion battery
CN110518246A
Negative pole piece as well as preparation method and application thereof
CN116387455A
Negative electrode material with long circulation and fast charge and containing nano interface layer and preparation method thereof
CN117199275A
Cited By
Core-shell material, preparation method thereof and negative electrode material
CN120901282A
A core-shell material and a preparation method thereof, and a negative electrode material
CN120901282B